E-211 Aneurysm size and impact on middle cerebral artery pressure: changes following flow diversion. (4th August 2020) - Brunozzi, D; See, A; Alaraj, A
Abstract : Background: The impact of cerebral aneurysm size on distal intracranial hemodynamics such as pressure is not completely understood, either before or after flow diversion (FD). Objective: To assess the impact of aneurysm size on distal pressure before and after FD.METHODS Beginning in December 2015, prospective measurement of middle cerebral artery (MCA) pressure was completed in consecutive patients with unruptured cerebral aneurysms in the ophthalmic to communicating segments of the internal carotid artery which were treated with a single FD. Pressure was recorded at the M1 segment ipsilateral to the cerebral aneurysm. Ratio of MCA to radial arterial pressure (pressure ratio, PR) controlled for variations in systemic blood pressure. Correlation between aneurysm size and MCA PR was assessed before and after treatment. Results: 29 aneurysms were treated in 27 patients. Mean aneurysm size was 7.4 mm (2–27 mm). Aneurysm size correlated linearly with systolic PR (1% per mm, p=0.001, r 2 =0.33; figure 1A ) and mean PR (0.6% per mm, p=0.03, r 2 =0.17; figure 1B ). After FD, aneurysm size continued to have a linear correlation with the systolic PR (1% per mm, p=0.004, r 2 =0.28; figure 1A ), but not with the mean PR (0.4% per mm, p=0.15, r 2 <0.1; figure 1B ). Conclusion: Aneurysm size affects distal hemodynamics: patients with larger aneurysms have increased systolic and mean MCA PR. After FD, mean MCA PR no longer associates with the aneurysm size, suggesting an effect of the FD on distal intracranial hemodynamics. Disclosures: D. Brunozzi: None. A. See: None. A. Alaraj: 1; C; NIH. 2; C; Cerenovus, Siemens.